Challenges and Readiness of Elementary School Teachers in the Implementation of the Merdeka Curriculum - Retnowati, Ayu Ana Fitri; Triyanto, Triyanto; Matsuri, Matsuri (Universitas Sebelas Maret, 2024)
This study explores the challenges faced by elementary school teachers in implementing the Merdeka Curriculum. In the era of globalization, education is becoming increasingly complex, emphasizing not only academic aspects but also the adaptability of graduates to the changing world. The aim of this research is to determine the challenges faced by teachers and the readiness of teachers in implementing the independent curriculum. The research employs a qualitative descriptive approach to investigate the preparedness of elementary school teachers in implementing the Merdeka Curriculum. Data collection techniques include observation, interviews, and document analysis. The evaluation of readiness encompasses indicators such as understanding the curriculum structure, planning, the learning process, module preparation, and assessment. Triangulation techniques ensure data accuracy. The findings reveal that teachers exhibit good readiness in planning and conducting lessons aligned with the Merdeka Curriculum. They comprehend the curriculum's principles and actively engage in developing lesson plans following the prescribed standards. Despite this positive outlook, challenges arise in terms of understanding and integrating key concepts, utilizing technology, and adapting assessment methods.